TEM based applications in solid state nanopores: From fabrication to liquid in-situ bio-imaging. (November 2022) - Muhammad Sajeer P; Simran; Nukala, Pavan; Manoj M. Varma
Abstract: Nanopore-based techniques are widely used owing to their diverse applications such as DNA sequencing, ion detection, gas filtration, protein sequencing, and numerous other applications. Although commercialized sequencing methods are based on biological nanopores, solid-state nanopore technology is emerging due to its several advantages over biological nanopores, such as its tunable size, chemical and mechanical stability, and possibilities for easy integration with measurement electronics. The unavailability of rapid, low-cost, easy solid-state nanopore fabrication methods with industrial scalability is one of the current bottlenecks in this domain. Among all nanopore fabrication techniques, the Transmission electron microscope (TEM) based fabrication method is frequently used in research labs due to its capability of drilling and tuning nanopores with high accuracy. Given that there are no other methods capable of imaging and fabricating nanopores simultaneously, it is important to discuss the related methods and protocols of TEM. This review focuses on the various aspects of nanopore technology using TEM, from pore fabrication to imaging. Hybrid nanopores are also emerging, which combine the benefits of biological and solid-state nanopores. These can be formed by integrating DNA origami with solid-state nanopores. Creating and imaging DNA origami structures also presents several challenges. We also review DNA origami imaging using conventional TEM. We hope that this review will provide a one-stop reference to TEM applications on solid-state nanopores from fabrication to bioimaging and boost further research in this area.